De Smith's judicial review - De Smith, S. A. (Stanley A.); Woolf, Harry, Sir, 1933-; Jowell, Jeffrey L.; Le Sueur, A. P. (Andrew P.); Donnelly, Catherine M. (Catherine Mary), 1974-; De Smith, S. A. (Stanley A.) (London : Sweet & Maxwell, 2007)
This title may be have a supplemental service whereas subscription order will be needed for the supplements. upon receipt supplements to be checked-in HRec for corresponding editions.
Rev. ed. of: Judicial review of administrative action. 5th ed. 1995.
Includes bibliographical references and index.
Keywords: Judicial review of administrative acts -- United Kingdom